Heat-induced seizures, premature mortality, and hyperactivity in a novel Scn1a nonsense model for Dravet syndrome - Mavashov, Anat; Brusel, Marina; Liu, Jiaxing; Woytowicz, Victoria; Bae, Haneui; Chen, Ying-Hsin; Dani, Vardhan S.; Cardenal-Muñoz, Elena; Spinosa, Vittoria; Aibar, José Ángel; Rubinstein, Moran (Frontiers in Cellular Neuroscience, 2023)
Dravet syndrome (Dravet) is a severe congenital developmental genetic epilepsy caused by de novo mutations in the SCN1A gene. Nonsense mutations are found in ~20% of the patients, and the R613X mutation was identified in multiple patients. Here we characterized the epileptic and non-epileptic phenotypes of a novel preclinical Dravet mouse model harboring the R613X nonsense Scn1a mutation. Scn1aWT/R613X mice, on a mixed C57BL/6J:129S1/SvImJ background, exhibited spontaneous seizures, susceptibility to heat-induced seizures, and premature mortality, recapitulating the core epileptic phenotypes of Dravet. In addition, these mice, available as an open-access model, demonstrated increased locomotor activity in the open-field test, modeling some non-epileptic Dravet-associated phenotypes. Conversely, Scn1aWT/R613X mice, on the pure 129S1/SvImJ background, had a normal life span and were easy to breed. Homozygous Scn1aR613X/R613X mice (pure 129S1/SvImJ background) died before P16. Our molecular analyses of hippocampal and cortical expression demonstrated that the premature stop codon induced by the R613X mutation reduced Scn1a mRNA and NaV1.1 protein levels to ~50% in heterozygous Scn1aWT/R613X mice (on either genetic background), with marginal expression in homozygous Scn1aR613X/R613X mice. Together, we introduce a novel Dravet model carrying the R613X Scn1a nonsense mutation that can be used to study the molecular and neuronal basis of Dravet, as well as the development of new therapies associated with SCN1A nonsense mutations in Dravet.